2004
DOI: 10.1103/physrevb.70.184525
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Josephson current qubits using a connecting loop

Abstract: We propose a coupling scheme for the three-Josephson junction qubits which uses a connecting loop, but not mutual inductance. Present scheme offers the advantages of a large and tunable level splitting in implementing the controlled-NOT (CNOT) operation. We calculate the switching probabilities of the coupled qubits in the CNOT operations and demonstrate that present CNOT gate can meet the criteria for the fault-tolerant quantum computing. We obtain the coupling strength as a function of the coupling energy of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Hence the effective potential in Eq. ( 12 ) becomes which describes the inductive energies of three loops with geometric inductance and the Josephson junction energies 25 , 31 , 32 , complying with the intuitive picture.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Hence the effective potential in Eq. ( 12 ) becomes which describes the inductive energies of three loops with geometric inductance and the Josephson junction energies 25 , 31 , 32 , complying with the intuitive picture.…”
Section: Resultsmentioning
confidence: 74%
“…The precise fluxoid quantization condition of superconducting loop reads with being the average velocity of Cooper pairs, the Cooper pair charge, and the Cooper pair mass 24 , 25 . The total magnetic flux threading the loop is the sum of the external and the induced flux .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several schemes for tunable qubit-qubit coupling have been proposed [40][41][42][43][44][45][46][47][48] following the original proposal by Makhlin et al [32]. We fabricated the design Fig.…”
Section: Tuneable Flux Qubit Couplingmentioning
confidence: 99%
“…Especially, we use a phase coupling by introducing a connecting wire between the two qubit loops (see Fig. 1) [10] because the phase coupling gives more controllable parameters than the inductive coupling with respect for the manipulation of qubit states [11]. It is shown that the Josephson junction in the connecting superconducting wires plays a role of controller in determining exchange interactions between the two qubits.…”
mentioning
confidence: 99%